Moving toward a Comprehensive Program of Critical Social Justice Teacher Education: A QuantCrit Analysis of Preservice Teachers' Perceptions of Social Justice Education. Issue 2 (3rd April 2023) - Wronowski, Meredith L.; Aronson, Brittany; Reyes, Ganiva; Radina, Rachel; Batchelor, Katherine E.; Banda, Rachael M.; Rind, Gul
Abstract: This study utilizes a QuantCrit framework to accomplish three goals: (1) describe a curricular and pedagogical redesign of teacher education courses grounded in social justice teaching (SJT), (2) discuss a Critical Social Justice Teaching instrument we used to measure attitudes and behaviors of preservice teachers (PSTs) as a result of these changes, and (3) present a quasi-experimental analysis to show changes in PSTs' CSJ dispositions following engagement in our redesigned coursework and teaching efforts. Significant changes in PSTs' CSJs' dispositions were observed after completion of a single redesigned course and increased minimally after completing additional courses. However, changes were related to PSTs' identity characteristics including race, gender, and religious practice.